2016
DOI: 10.1111/jocn.13438
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing the Braden scale for pressure ulcer risk among medical inpatients: the contribution of self‐reported symptoms and standard laboratory tests

Abstract: Nurses play a key role in preventing pressure ulcers during hospitalisation. A better understanding of the underlying mechanisms may improve the quality of care. Knowledge about symptoms associated with pressure ulcer risk may contribute to a faster clinical judgment of patients at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 41 publications
3
42
0
5
Order By: Relevance
“…shown to be at an increased risk for HAPI. Schoonhoven et al, 2006;Raff et al, 2016;Slowikowski & Funk, 2010;Aljezawi et al, 2014;Connor, Sledge, Bryant-Wiersema, Stamm, & Potter, 2010;Corniello et al, 2014;Bredesen, Bjoro, Gunningberg, & Hofoss, 2015;Brito, Vasconcelos Generoso, & Correia, 2013;Skogestad et al, 2017;Sardo et al, 2016;Delmore et al, 2015;Cowan et al, 2012;Rao et al, 2016;Fred, Ford, Wagner, & VanBrackle, 2012;Hyun et al, 2014;Man & Au-Yeung, 2013;Saunders et al, 2012;Smit et al, 2016;Yoshimura et al, 2015;Demarre et al, 2015;Baumgarten et al, 2006;…”
Section: Tissue Tolerancementioning
confidence: 99%
“…shown to be at an increased risk for HAPI. Schoonhoven et al, 2006;Raff et al, 2016;Slowikowski & Funk, 2010;Aljezawi et al, 2014;Connor, Sledge, Bryant-Wiersema, Stamm, & Potter, 2010;Corniello et al, 2014;Bredesen, Bjoro, Gunningberg, & Hofoss, 2015;Brito, Vasconcelos Generoso, & Correia, 2013;Skogestad et al, 2017;Sardo et al, 2016;Delmore et al, 2015;Cowan et al, 2012;Rao et al, 2016;Fred, Ford, Wagner, & VanBrackle, 2012;Hyun et al, 2014;Man & Au-Yeung, 2013;Saunders et al, 2012;Smit et al, 2016;Yoshimura et al, 2015;Demarre et al, 2015;Baumgarten et al, 2006;…”
Section: Tissue Tolerancementioning
confidence: 99%
“…It is recognised that older patients, patients with diabetes and patients who are bedfast are at higher risk for pressure ulcer (Coleman et al., , ; Fife et al., ; Sving, Idvall, Hogberg, & Gunningberg, ). Moreover, factors such as haematological, nutritional and general health status have been associated with pressure ulcer risk (Brito, de Vasconcelos Generoso, & Correia, ; Coleman et al., ; Langer & Fink, ; Skogestad et al., ). The magnitude of potential risk factors makes it difficult to develop generic risk assessment tools, and few studies add evidence about the preventive impact of risk assessment tools (Moore & Cowman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mainly, contributing factors are associated to the patient's condition, health care provider and health care delivery system [29]. A review of several studies, aimed to identify factors related to the pressure ulcer in clinical setting, indicated that immobility [5,16,[30][31][32], length of hospital stay [16,30,[32][33][34][35], Older age [16,30,36],reduced sensory perception [16,33,36,37], fecal and urinary incontinence [36,38], worse Braden scores [6,30,36,[39][40][41], comorbidity [6,30], and nutrition [31,37,40,42,43] was found to be statically significant risk factor for PU. However, repositioning would reduce the magnitude of pressure over vulnerable areas of the body [1].…”
Section: Introductionmentioning
confidence: 99%